2014
DOI: 10.1111/jnp.12039
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychological profile of vascular cognitive impairment not demented: A meta‐analysis

Abstract: The most common cause of vascular cognitive impairment not demented (VCIND) is cerebral small vessel disease leading to diffuse subcortical white matter lesions. While many studies indicate that the core cognitive features of VCIND are executive dysfunction and impaired processing speed, this finding is not always consistent, and may be partially dependent on the comparison group applied. Hence, we undertook two systematic meta-analytic reviews on neuropsychological test performance across eight cognitive doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 116 publications
10
103
2
3
Order By: Relevance
“…When assessing global cognitive function, the MoCA may be more useful than the MMSE for detecting cognitive impairment particularly in early stages of VCI [42]. Previous research has suggested that fluid abilities (e.g., information processing speed) may be more vulnerable to cerebrovascular dysfunction than crystallised abilities, at least at non-severe impairment stages [7,43]. Therefore, VCI-ND prevalence rates may be higher if the definition of VCI-ND includes impairment of fluid abilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When assessing global cognitive function, the MoCA may be more useful than the MMSE for detecting cognitive impairment particularly in early stages of VCI [42]. Previous research has suggested that fluid abilities (e.g., information processing speed) may be more vulnerable to cerebrovascular dysfunction than crystallised abilities, at least at non-severe impairment stages [7,43]. Therefore, VCI-ND prevalence rates may be higher if the definition of VCI-ND includes impairment of fluid abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular cognitive impairment, no dementia (VCI-ND) has been developed as a concept to capture individuals who are at the earliest stage of VCI and who may be at a higher risk of developing further cognitive decline and dementia [6]. VCI-ND is thought to be a pre-dementia state, yet while some individuals may go on to develop further cognitive decline or vascular dementia (VaD), others may return to a ‘normal, healthy' state of cognitive function [7]. The differences in progression rates to dementia between individuals with VCI-ND may be due to inconsistencies in the operationalization of VCI-ND across studies including: whether individuals with pure or mixed [e.g., with Alzheimer's disease (AD)] pathology are included in the definition; differences in the underlying causes of the vascular pathology, such as large- or small-vessel diseases leading to ischaemic strokes, white matter lesions, hypoperfusion or haemorrhage [8], and the cognitive domains investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The VCI construct includes not only vascular dementia (VaD), but also mixed dementia (vascular and degenerative) and vascular cognitive impairment-no dementia (VCI-ND), which refers to a subgroup of patients who manifest cognitive decline resulting from cerebrovascular injury but do not satisfy the diagnostic criteria of dementia [1, 2]. In addition to cognitive impairment, mainly involving processing speed and executive functioning [6], VCI patients also show behavioral (i.e., apathy, irritability, psychomotor agitation, disinhibition, and aberrant motor behavior) and mood deficits (namely depression, with or without anxiety) that correlate with worsening of both cognitive and functional status [7]. Moreover, strokes of the basal ganglia and internal capsule increase significantly the risk of poststroke depression and executive dysfunction [8].…”
Section: Introductionmentioning
confidence: 99%
“…During the progression of the disease, cerebral arteries harden, resulting in a deficient nutrient delivery to the cerebral parenchyma. This in turn, causes metabolic distress and bioenergetic disturbances that contribute to cerebral degeneration (Vasquez and Zakzanis, 2015). There are several models to induce hypoperfusion in experimental animals based on the occlusion of two (Bottiger et al, 1998; Bottiger et al, 1999), three (Carmichael, 2005; Thal et al, 2010; Onken et al, 2012) or four (Pulsinelli and Buchan, 1988; Traystman, 2003) vessels.…”
Section: Introductionmentioning
confidence: 99%